Carbon Diffusion: Au Catalyzed Carbon Diffusion in Ni: A Case of Lattice Compatibility Stabilized Metastable Intermediates (Adv. Funct. Mater. 21/2018). (May 2018) - Kang, Jian‐Xin; Zhang, Dong‐Feng; Guo, Gen‐Cai; Yu, Hai‐Jun; Wang, Li‐Hua; Huang, Wei‐Feng; Wang, Ru‐Zhi; Guo, Lin; Han, Xiao‐Dong
Abstract : The stabilization of the unstable fcc‐Ni x C by taking advantage of the epitaxial growth to elevate the structure transformation energy barrier using Au as the substrate is presented for the first time by Donfeng Zhang, Lin Guo, Xiao‐Dong Han, and co‐workers in article number1706434 . The introduction of Au promotes the carbon diffusion in Ni and the thereby graphitic carbon growth.